LA TOPONIMIA DE LA REGIÓN DE MURCIA. TRATAMIENTO INFORMÁTICO Y PERSPECTIVAS - Verdú Conesa, Isidro (Antigüedad y Cristianismo, 1995)
In our days the computers have facilitated the work load and have made possible avances in a variety of disciplines, arnongst them the Humanities. One of the linguistic fields wich could resolve numerous problems is the study of the place names. We present in this article our contribution to the application of the computer sciences to the study and elaboration of this field. The system developed is not only oriented to facilitate the editing of a book on place names but also is a source of information. It is specially usefull in helping the students amd investigators find the information using Search Keys different from those used in the edition of the book. We also explain some of possible future extensions such as the informatic connection whith place names of other geographic areas, th use of the artificial inteligente to find the roots and facilities for analysing the texts.